Science Teaching: Recommendations and its Implications on Teacher Education Programme - Koireng, R. R. (Voices of Teachers and Teacher Educators, 2017)
Policy statements suggest teaching of science as an integrated subject till secondary stage. This paper discusses about the recommendation of science teaching from upper primary to secondary stage. The recommended pedagogy and teaching learning materials including its implications on teacher preparation programmes prevailing in the country are discussed here.